ANALISIS SWOT TENTANG STRATEGI PEMASARAN AGRIBISNIS DI PULAU SETOKOK (STUDI KASUS KOMODITAS SEMANGKA) - Harlan, Fandy Bestario; Wirawan, Adhitomo; Maulida, Nur Alifia (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2021)
This study aimed to analyze the concept of the most appropriate marketing strategic to be applied to the Agribisnis Semangka Batam of Kepulauan Setokok Batam. This research uses descriptive analysis with qualitative approach. The data sources used in this analysis are primary data from respondents and secondary data from company documents. The technical analysis of the data used is carried out through SWOT analysis. The results show that the position Agribisnis Semangka in unit I using the SWOT chart indicates that the outcome of the analysis is positive, and the correct strategy at this position is the